Qualitative Characters Diversity of Prentul Kediri Cayenne Pepper Mutant (M1) Resulted from Gamma Ray Mutation Induction - Rohcahyani, Fadilla Eka; Moeljani, Ida Retno; Suhardjono, Hadi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Prentul Kediri cayenne pepper is a local variety that has the potential to be developed into a new superior variety through the breeding of gamma-ray mutations. The purpose of the study is to find out the diversity and degree of similarity in plants of the M1 generation based on qualitative character. The research was conducted in August 2021-February 2022 at the research field, Ketindan Village, Malang City. This study was conducted in a completely randomized block design with three replications. Data was subjected to cluster analysis using the NTSYSpc.2.02i program. The results showed that induction of gamma-ray mutations led to phenotype diversity in several qualitative characters, namely plant habitus, leaf shapes, and fruit shapes, while two other characters, i.e., fruit calyx and the position of flowers remained uniform. The degree of intermutants at each dose of gamma ray mutation is varied. Qualitative characters that remained uniform in the mutant population (M1) were the calyx character of the fruit and the position. In the mutant population (M1), the results of mutations in gamma rays at doses of 100 Gy and 200 Gy were still found in individuals with characters 100% similar to control plants. Meanwhile, in the mutant population (M1), the results of mutations in gamma rays at a dose of 300 Gy were not found to have individuals with characters 100% similar to control plants. Keywords: Gamma ray, Mutation diversity, Prentul Kediri Cayenne Pepper